Analysis of growth and reproduction of yellowstripe scad (Selaroides leptolepis) - La Nane (Tomini Journal of Aquatic Science, 2021)
The waters of Tomini Bay are waters that have quite a lot of natural resources. One of the resources in these waters is the yellowstripe scad fish (Selaroides leptolepis). This observation aims to study the reproductive biology aspects of the yellowstripe scad fish, including length and weight, sex ratio, gonadal maturity level, gonadal maturity index, and fecundity in order to provide information for planning options for the management of yellowstripe scad fish resources so that they can be utilized optimally and sustainably. The observation was conducted on May 4, 2019. Fish sample analysis was carried out at the Hydrobiology and Biometrics Laboratory, Gorontalo State University. The results of the observation showed that the average length of the yellowstripe scad fish was 200 mm and the weight was 104.5 g. The length-weight relationship of yellowstripe scad fish (Selaroides leptolepis) is categorized as negative allometric with b = 1.04. The gonadal maturity index of male yellowstripe scad fish ranged from 0.008-0.034, while in females it ranged from 0.011-0.056. The average condition factor of male and female fish is 0.9962, respectively.